Strategi Mengatasi Masalah Kesehatan dan Lingkungan Hidup di Pemukiman Kumuh Lewat Program Pemasaran Sosial - Pudjiastuti, Wahyuni (Makara Human Behavior Studies in Asia, 2002)
The research has a starting point from assumption that compose accurate social marketing strategy is being needed to overcome social health and environmental problems in the sleim settlement area in Jakarta. The strategy should consider the condition of target area, target adopters and some factors that influence in the community participation to some social products. The research was done in three sleims area, (i) narrow street, (ii) flood plain river and along the railway track. The research was designed as descriptive research correlation which is analyzed by multiple regression and distribution frequency table. The result of the research is being used as material for compilling social marketing strategy. The component strategy consist of consideration of marketing mix and communication elements.